Mark’s Endings in Context: Paratexts and Codicological Remarks - Mina Monier (Religions, 2022)
This article addresses the problem of the perception of Mark’s endings as expressed in its manuscript tradition. I will argue that, unlike the modern standardized image, manuscript evidence offers a complex phenomenon in which the endings were perceived in diverse ways that move across the threshold that separates a text from paratexts. Further, the manuscripts show an influence between the endings and their associated paratexts. I will show this phenomenon by examining (i) the hypotheses before the Gospel, (ii) marginalia that engaged Mark 16, and (iii) postscripts after the Gospel. In conclusion, the article recommends revisiting the standard perception of the “endings” within their larger paratextual ecosystem.